Relationship Between the Variety of Complementary Foods (MP-ASI) for Children Aged 6-24 Months and Incidence of Stunting - Prawira, I Nyoman Dio Yudha; Nurbaiti, Lina; Paramaiswari, Nurul Firdausi (Jurnal Biologi Tropis, 2025)
The first 6–24 months of life is a critical “golden period” of rapid growth during which adequate and diverse nutrition is crucial. Low dietary diversity during the introduction of complementary foods (MP-ASI) can increase the risk of chronic malnutrition and stunting, and the persistently high prevalence of stunting in Central Lombok motivates investigation into the role of MP-ASI variation on linear growth. This cross-sectional, observational analytical study aimed to determine whether MP-ASI variation is associated with stunting in children aged 6–24 months in the Puyung Community Health Center area. Data were collected from October–December 2024 on ninety mother-child pairs or caregivers selected using stratified random sampling. Of the 90 children, 26 (28.9%) had inadequate MP-ASI variation (<5 food groups/day) and 49 (54.5%) were classified as stunted. Bivariate analysis using chi-square test showed no statistically significant association between variations in complementary feeding and stunted growth (p = 0.693). Variations in complementary feeding were not significantly associated with stunted growth in children aged 6–24 months in the Puyung Community Health Center area. Nutrition programs should continue to promote dietary diversity in addition to interventions that address sanitation, maternal nutrition, and other contextual determinants of stunted growth.